Repeatability and reproducibility of maximum diameter measurements of prostate lesions on MRI with repositioning and variation of imaging sequences: a test-retest study - Zhang, Kevin Sun; Glemser, Philip Alexander; Neelsen, Christian; Wennmann, Markus; Rotkopf, Lukas Thomas; Netzer, Nils; Meinzer, Clara; Hielscher, Thomas; Weru, Vivienn; Görtz, Magdalena; Stenzinger, Albrecht; Hohenfellner, Markus; et al. (Magnetic resonance imaging, 2026)
Objectives - To assess variability of maximum diameter measurements of prostate lesions in MRI assessing patient repositioning, rater and sequence effects. - Methods - Forty-two patients were included retrospectively, who received a clinical bi−/multiparametric prostate MRI examination and agreed to have the T2-weighted (T2WI) and diffusion weighted-imaging (DWI) sequences scanned twice. Maximum diameter measurements of prostate lesions mentioned in the clinical radiologist reports were performed by four readers in multiple reading sessions for determination of inter-sequence (between two DWI sequences), inter-scan (between clinical and additional scan), intra-rater and inter-rater variability. The primary calculated metrics were the repeatability and reproducibility coefficient (RC/RDC), including pooled RC/RDC. - Results - Variability measured by RCs/RDCs was lowest for measurements obtained within the same reading session, with inter-scan RCs up to 5.6 mm/6.5 mm for T2WI/DWI, pooled RCs of 4.8 mm/5.8 mm, respectively, and inter-sequence RDCs of 5.4 mm-5.9 mm, pooled RDC 5.8 mm. Measurements performed in separate reading sessions demonstrated significantly higher variability for both settings in the majority of cases (RCs: up to 10.9 mm/11.7 mm/10.2 mm for T2WI/DWI/inter-sequence, p ≤ 0.002), pooled RCs/RDCs 9.2 mm-9.9 mm. Measurements necessarily generated in different reading sessions, i.e., intra-rater or inter-rater, demonstrated high variability (RCs/RDCs up to 11.4 mm/11.5 mm for T2WI/DWI). - Conclusions - Prostate lesion measurements demonstrate considerable variability. When measured in one reading session by one rater, lesion diameter differences below the pooled RCs of 4.8 mm, 95 %-CI [3.9, 5.6] for T2WI and 5.8 mm, 95 %-CI [4.7, 7.1] for DWI should not necessarily assumed to be true biological change, as these differences may result from measurement- or repositioning-based variability alone. Caution needs to be taken assessing size changes.